Thermodynamics of a pseudospin-electron model without correlations - Stasyuk, I.V.; Shvaika, A.M.; Tabunshchyk, K.V. (Condensed Matter Physics, 1999)
Thermodynamics of a pseudospin-electron model without correlations is investigated. The correlation functions, the mean values of pseudospin and particle number, as well as the thermodynamic potential are calculated. The calculation is performed by a diagrammatic method in the mean ﬁeld approximation. Single-particle Green functions are taken in the Hubbard-I approximation. The numerical research shows that an interaction between the electron and pseudospin subsystems leads in the µ = const regime to the possibility of the ﬁrst order phase transition at the temperature change with the jump of the pseudospin mean value 〈Sz〉 and reconstruction of the electron spectrum. In the regime n = const, an instability with respect to phase separation in the electron subsystem can take place for certain values of the model parameters.